Making nanomaterial-enabled nitrate sensors useful for real water systems: user-centric design perspectives - Shelby Defeo; Samuel Erickson; Maria F. Perez Mendoza; Alexia Cooper; Bruce Barrios; Zachary Malone; Ryan D. Baxter; Sayantani Ghosh; Thomas C. Harmon (Frontiers in Sensors)
Water quality monitoring is essential for identifying risks to environmental and human health. Nitrate monitoring is of particular importance, as its anthropogenic point and nonpoint sources are common globally and have deleterious effects on water quality and usability as well as aquatic ecosystem health. Standard methods for assessing nitrate concentrations in water generally involve laboratory techniques, as methods available for field testing face significant tradeoffs between cost, precision, and portability. Given its relatively ubiquitous nature and the widespread regulation of nitrate pollution, it is a prime target for sensor development. The growing field of nanomaterials (e.g., nanoparticles, nanotubes, and 2-dimensional materials) offers the potential to eliminate these tradeoffs through a new generation of field-ready nitrate sensors. However, transitioning nano-sensors from the lab to the field remains challenging. In this perspective we examine the challenges of lab-to-field transition of nano-sensors for nitrate, highlighting the importance of a user-centered design approach under the framework of FOCUS (form factor, operational robustness, cost, user interface, and sensitivity).